VARIETAL ADAPTATION AND PERFORMANCE OF SHALLOT UNDER FLOATING CULTIVATION WITH CHICKEN MANURE APPLICATION IN TROPICAL LOWLAND WETLANDS - Susilawati, Susilawati; Sodikin, Erizal; Harun, M Umar; Irmawati, Irmawati (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Shallot (Allium ascalonicum L.) can be cultivated across a wide range of altitudes, from lowlands to highlands; however, production in Indonesia is predominantly conducted on dryland areas. In response to the national program promoting shallot production expansion outside Java, the development of shallot cultivation in South Sumatra faces challenges due to extensive wetland conditions. Floating cultivation systems offer a potential alternative for optimizing wetland utilization. This study aimed to evaluate the adaptability and performance of several shallot varieties under floating cultivation with different rates of chicken manure application. Plant analysis was carried out at the Plant Physiology Laboratory, and the experiment was carried out from June to August 2024 at the Embung (research reservoir) and Experimental Garden, Faculty of Agriculture, Sriwijaya University, Indralaya. A randomized block design with two factors and three replications was applied. The first factor consisted of four shallot varieties (Tajuk, Bauji, Batu Ijo, and Bima Brebes), while the second factor involved chicken manure rates of 0, 10, 20, and 30 t ha⁻¹. Data were analyzed using RStudio and presented in tables and figures. The results showed that the Bauji variety exhibited superior growth and yield compared to the other varieties. Increasing chicken manure application up to 20 t ha⁻¹ significantly improved shallot growth and productivity. It can be concluded that the Bauji variety, combined with 10 t ha⁻¹ chicken manure, is suitable for cultivation using a floating system in tropical wetlands.